Interconnection of Velue Sphere and Addictive Behavior in Adolescence - Krapyva, Mariia; Pysmenna, Alina (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2025)
In the period of adolescence, characterized by an identity crisis and an active search for  own "I," addictive behavior can act as a kind of temporary way to overcome internal tension, reduce emotional discomfort and restore a subjective sense of well-being, despite possible negative consequences for the physical, mental, social and spiritual health of an individual. In conditions of war conflict, unstable socio-economic situation and general decrease in the sense of security, age-related crises are especially aggravated, which increases the risks of the formation of destructive strategies of behavior among young people. Young men, due to an insufficiently formed value system, immature mechanisms of self-regulation and increased emotional vulnerability, are more inclined to use addictive models as  means of achieving internal balance.  In the proposed article, a theoretical analysis of addictive behavior formation problem in adolescence is carried out, attention is focused on the relationship between the value sphere of an individual and the tendency to dependent forms of response. The results of an empirical study confirming the existence of a statistically significant relationship between individual value orientations and the level  of risk to develop addictive behavior  are presented. On the basis of the obtained results, the need to develop and implement targeted psychoprophylactic measures is substantiated. The article offers an author's training program aimed at developing adaptation resources of young men, increasing awareness of their own life priorities and the formation of constructive ways to overcome stressful situations. The implementation of such programs has a preventive effect and can significantly reduce the level of addictive behavior among young people in the conditions of modern social challenges. The psychological methods used include empirical (questionnaires) and mathematical statistics methods (descriptive statistics, Pearson's correlation analysis).